Intelligent Energy Management in an Isolated DC Microgrid using Fuzzy Logic - Youssfi Abdelaziz; El Kadi Youssef Ait (EPJ Web of Conferences)
An intelligent management system based on fuzzy logic is proposed in this work to optimize energy management in a DC microgrid. The main objective is to guarantee the continuous supply of a DC load, to favor the use of energy produced by renewable sources, and to optimize the operation of the storage unit. The microgrid studied consists of a distributed generation unit in the PV modules and an ESS using a Lithium-Ion battery, both connected to the load. The PV system is controlled by a MPPT method implementing the INC algorithm, while the storage system is managed by a PI controller to control battery charging and discharging. A detailed explanation of the system is followed by a Matlab/Simulink simulation, which validates the proposal. Simulation results demonstrate the system's reliability, high performance and fast dynamics. More specifically, the performance indicators show a significant improvement in energy efficiency, a reduction in energy losses, and increased stability of the microgrid. These features confirm the effectiveness of the proposed control strategy for energy management in an isolated DC microgrid.